PERAN UNDANG UNDANG TERHADAP ANALISIS PANCASILA - Abdi Fristho Hutasoit; Fahrysyah Aulya, Griyani Elisabeth Purba, Joy Prana Bangun, Santiana Siboro, Ramsul Nababan, Maulana (ADMIN: Jurnal Administrasi Negara, 2024)
Laws have an important role in encouraging and influencing the analysis of Pancasila. Pancasila as the basis of the Indonesian state requires a deep and contextual understanding so that it can be applied effectively in national and state life. Laws that are directly related to Pancasila cover various aspects of people's lives. One of them is the 1945 Constitution of the Republic of Indonesia. This law is the highest legal basis in Indonesia and regulates the values of Pancasila which must be upheld by all citizens. Apart from the Constitution, there are also other regulations that directly or indirectly influence the analysis of Pancasila. Examples are the Law on Education which regulates character education based on Pancasila, as well as the Law on Culture which protects and preserves Indonesian cultural values based on Pancasila. The role of legal analysis of Pancasila can also be seen in the legislative process. When a law is discussed and passed, the Pancasila aspect becomes one of the main considerations in determining the policies and regulations that will apply. In this case, the law has an important role in ensuring that the values of Pancasila are realized in everyday life. However, the role of the Law in the analysis of Pancasila also has its own challenges. For example, in some cases, the interpretation and implementation of the Law can be complicated and give rise to differences of opinion. Therefore, synergy is needed between law and Pancasila analysis in order to achieve the common goal of building a harmonious national and state life. Laws have an important role in encouraging and influencing the analysis of Pancasila. The basic law is the law that regulates the values of Pancasila and ensures their implementation in everyday life. However, the challenges of interpretation and implementation also need to be overcome so that Pancasila can become a strong guideline in carrying out national and state life.